Abdominal plasty with and without plication-effects on trunk muscles, lung function, and self-rated physical function. Issue 3 (4th May 2017) - Wilhelmsson, Sofia; Fagevik Olsén, Monika; Staalesen, Trude; Elander, Anna; Nygren-Bonnier, Malin
Abstract: Background: Weight loss after obesity and pregnancy is associated with excess abdominal skin and weakness of the abdominal wall, which is assumed to cause low back pain and reduce lung function. Today, abdominoplasty is the only known method to treat excess skin, and plication is used to improve aesthetics and function alone or in addition to surgery. There is lack of evidence concerning the surgery's effect on trunk muscles, lung function, and physical function. The aim was to evaluate the effect on trunk muscle endurance, lung function and self-rated physical function after abdominoplasty with and without muscle plication. Aim: To evaluate the effect on trunk muscle endurance, lung function, and self-rated physical function after abdominoplasty with and without muscle plication. Methods: A series of 125 people were randomised to abdominoplasty with or without rectus abdominis muscle plication. Trunk muscle endurance, lung function, and self-rated physical function (disability rating index) were measured before and 1 year after surgery. Results: There were no significant differences in any of the measured variables between the groups either before or after surgery. A significant decrease ( p = .02) in back muscle endurance was seen after abdominoplasty without muscle plication. A significant positive effect ( p = .04) in one of the activities (running) assessed by DRI was reported after abdominoplasty with muscle plication. Conclusions: No significant differences in trunk muscle endurance, lung function, or self-rated physical function were found after abdominoplasty with vs without plication. As the primary indication for surgery was excess skin and not diastasis of the rectus abdominis muscles, there is a need for future trials before conclusions can be drawn of effect of abdominoplasty and plication.